Analisa Kandungan Hidroquinon dan Merkuri dalam Krim Malam Menggunakan High Perform Liquid Chromatography (HPLC) dan Inductively Coupled Plasma Mass Spectrometry (ICP-MS) - Mutawalli Sjahid Latief (Syntax Corporation Indonesia, 2021)
Hydroquinone is used clinically as a topical agent for depigmented conditions such as chloasma and melasma, but use of more than 2% hydroquinone can cause irritation. Hydroquinone levels exceeding 5% can cause a burning sensation on the skin. Mercury in the smallest levels can be toxic, the use of high doses can cause permanent damage to the brain, kidneys and impaired fetal development. The purpose of this study was to identify and determine levels of hydroquinone and mercury in night creams from several beauty clinics in Tangerang. Samples were taken from five beauty clinics in Tangerang, Banten. Samples were analyzed using HPLC (High Perform Liquid Chromatography) to determine hydroquinone levels, while mercury levels were analyzed using ICP-MS (Inductively Coupled Plasma Mass Spectrometry). This research was conducted at the Regional Health Laboratory of DKI Jakarta.The results showed that from 5 samples that analyzed, cream B containing 4,87 % hydroquinone, cream D containing 4,64 % hydroquinone and cream E containing 5,23 % hydroquinone. The conclusion of this study is that the use of hydroquinone ingredients in night creams is still widely found, of the five samples there are three positive containing hydroquinone, namely with levels of 4.87%, 4.64% and 5.23%, while the use of mercury ingredients in night cream preparations is negative in all five samples.